Integrated prevention protocol to fight COVID-19: Creating a fine balance - Nitin P. Ghonge; Sanchita Dube Ghonge (Indian Journal of Integrative Medicine, 2022)
The pandemonium of COVID-19 pandemic is likely to have significant impact over the healthcare which may evolve with rise of ‘Evidence-based Lifestyle Medicine [eLSM]’. Integrated protocols based on lifestyle changes, which combine Modern Medicine and Ayurveda, may offer best protection against COVID-19. Ayurvedic practices may help in creating a non-specific ‘virus-hostile’ mucosal environment for strong local barrier to 2019-nCoV. The healing powers of Ayurvedic herbs can help to enhance body’s innate immunity which can provide strong systemic defense against COVID-19. Lifestyle choices and modifications are likely to play key role in protection against COVID-19. The ‘integrated protocol’ for protection against COVID-19 which is described in this article is backed with science and common-sense reasoning and reemphasizes the impact of lifestyle choices in our lives